2014
DOI: 10.18052/www.scipress.com/ilns.10.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anaerobic Exercise in the Morning and Evening Sessions on some Coagulation Factors in Non-Athletes Female Students of Islamic Azad University of Sanandaj

Abstract: The purpose of the present research is compare the effects of coagulation factors in non-athletes gilrs after exhaustive anaerobic activity sessions in the morning and evening. Present study was semiemprical that was done on 12 non-athlete female students in range of 18-24 years. Exercise protocol was RAST test, that in which each person passed amain 35 meters of distance for 6 times and rest 10 seconds between each stage. Blood sampling was performed Once in the morning (8 am) and a later week in evening (5 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…They also reported that the plt count was significantly higher in the morning. Tabatabai et al (22) reported no significant change in plt count in non-athlete female students after the rest protocol (6 sets of running at a maximum speed over a distance of 35 m with 10 s of rest between each set). In addition, there was no significant difference in plt count in the morning and afternoon (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported that the plt count was significantly higher in the morning. Tabatabai et al (22) reported no significant change in plt count in non-athlete female students after the rest protocol (6 sets of running at a maximum speed over a distance of 35 m with 10 s of rest between each set). In addition, there was no significant difference in plt count in the morning and afternoon (22).…”
Section: Discussionmentioning
confidence: 99%
“…Tabatabai et al (22) reported no significant change in plt count in non-athlete female students after the rest protocol (6 sets of running at a maximum speed over a distance of 35 m with 10 s of rest between each set). In addition, there was no significant difference in plt count in the morning and afternoon (22). Ghanbari-Niaki and Tayebi (23) showed that changes in plt count, MPV, PDW, and P-LCR were not significant in male university students after a session of low-intensity circular strength training.…”
Section: Discussionmentioning
confidence: 99%